Evidence for interactions between filaggrin null mutations and environmental exposures in the aetiology of atopic dermatitis is currently lacking. (5th March 2020) - Park, Y.M.; Seo, S.J.
Abstract : Linked Article: Blakeway et al. Br J Dermatol 2020; 183 :443–451 .